Гражданское общество как субъект кинологического обеспечения правоохранительной сферы - Селюков, В. С.; Seliukov, V. S.; ORCID: http://orcid.org/0000-0002-6690-6484 (Knowledge, Education, Law, Management. – 2020. – Vol. 2, № 4 (32). – P. 145-151, 2020)
Зазначено, що виходячи з того, що кінологічне забезпечення є досить широким за змістом поняттям, слід зазначити, що є кілька груп інститутів, які стосуються кінологічного забезпечення правоохоронної діяльності в Україні у контексті створення можливостей для реалізації прав громадян у сфері кінологічної діяльності та утримання домашніх тварин, а також захист їх інтересів. Наголошено, що кінологічна діяльність не може існувати без таких реальних впливових інститутів громадянського суспільства – ветеринарні установи, громадські організації, медичні установи – всі ці органи тим чи іншим чином розкривають потенціал собак, що надалі суспільство, зокрема державні суб'єкти правоохоронної діяльності, використовує на користь людства для забезпечення його безпеки та підтримання правопорядку.

The law enforcement sphere is very broad in its structure, the sphere of public relations, which undoubtedly encompasses public institutions. They can be considered the main and key subjects of cynological support, namely becausemost of the non-state cynological organizations in one way or another interact with the state ones, and in one way or another participate in law enforcement. It is worth noting that civil society itself cannot be the subject of the activity under study, therefore, the article focuses precisely on its key institutions – public organizations. In the context of the studied relations, special attention is paid to the meaning of such a concept as a civil society. The points of view of different scientists have been analyzed in order to determine the optimal content of the concept of “civil society” in the context of dog training for law enforcement. It is noted that based on the fact that cynological support is a fairly broad concept in its content, it is worth noting that there are several groups of institutions related to cynological support of law enforcement activities in Ukraine in the context of creating opportunities for the realization of citizens’ rights in the field of cynological activity and content pets, as well as protection of their interests. Cynological activity cannot exist without such real, influential institutions of civil society – veterinary institutions, public organizations, medical institutions – all these bodies in one way or another reveal the potential of dogs, which in the future society, including state law enforcement actors, use in the benefit of humanity to ensure its safety and the maintenance of law and order.

Проанализированы точки зрения разных ученых с целью определения оптимального содержания понятия «гражданское общество» именно в контексте кинологического обеспечения правоохранительной деятельности. Отмечено, что, исходя из того, что кинологическое обеспечение является достаточно широким по своему содержанию понятием, стоит отметить, что существует несколько групп институтов, имеющих отношение к кинологическому обеспечению правоохранительной деятельности в Украине в контексте создания возможностей для реализации прав граждан в сфере кинологической деятельности и содержания домашних животных, а также защита их интересов. Кинологическая деятельность не может существовать без таких реальных влиятельных институтов гражданского общества – ветеринарные учреждения, общественные организации, медицинские учреждения, – все эти органы тем или иным образом раскрывают потенциал собак, который в дальнейшем общество, в том числе государственные субъекты правоохранительной деятельности, использует в пользу человечества для обеспечения его безопасности и поддержания правопорядка.
Civil society as a subject of cynological support of the law enforcement sphere
Społeczeństwo obywatelskie jako podmiot świadczący usługi w zakresie egzekwowania prawa
Селюков, В. Гражданское общество как субъект кинологического обеспечения правоохранительной сферы / Вадим Селюков // Knowledge, Education, Law, Management. – 2020. – Vol. 2, № 4 (32). – P. 145-151. - DOI: https://doi.org/10.51647/kelm.2020.4.2.27.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; громадянське суспільство; civil society; гражданское общество; правоохоронна діяльність; law enforcement activity; правоохранительная деятельность; кінологічне забезпечення; cynological support; кинологическое обеспечение; громадські кінологічні інституції; public cynological institutions; общественные кинологические институции; canistherapy; каністерапія; канистерапия